Draft genome assembly for the colombian freshwater bocachico fish, Prochilodus magdalenae - Yepes-Blandón, Jonny Andrés; Bian, Chao; Benítez-Galeano, María José; Aristizabal-Regino, Jorge Luis; Estrada-Posada, Ana Lucía; Mir, Daiana; Vásquez-Machado, Gersson; Atencio-García, Víctor Julio; Shi, Qiong; Rodríguez-Osorio, Nélida (Frontiers in Genetics, 2023)
We report the first draft genome assembly for Prochilodus magdalenae, the leading representative species of the Prochilodontidae family in Colombia. This 1.2-Gb assembly, with a GC content of 42.0% and a repetitive content of around 31.0%, is in the range of previously reported characid species genomes. Annotation identified 34,725 nuclear gene models. Gene ontology and primary metabolic pathway annotations indicate similar gene profiles for P. magdalenae and the closest species with annotated genomes: blind cave fish (Astyanax mexicanus) and red piranha (Pygocentrus nattereri). A comparative analysis showed similar genome traits to other characid species. The fully sequenced and annotated mitochondrial genome reproduces the taxonomic classification of P. magdalenae and confirms the low mitochondrial genetic divergence inside the Prochilodus genus. Phylogenomic analysis using nuclear single-copy orthologous genes also confirmed the evolutionary position of the species. This genome assembly provides a high-resolution genetic resource for sustainable P. magdalenae management in Colombia and, as the first genome assembly for the Prochilodontidae family, will contribute to fish genomics throughout South America.